Keepers of Trauma: Rape Victim Advocates’ Secondary Traumatic Stress, Burnout, and Coping Techniques - Maier, Shana L. (Violence against women, 2024)
This qualitative research explores rape victim advocates’ secondary traumatic stress (STS), burnout, and coping strategies. Data reveal that the hardest parts of advocates’ work include feeling like they cannot help survivors, hearing survivors’ stories, and seeing the failings of the CJ and legal systems. Most advocates (81%) experience STS, evident in emotional and behavioral responses. Most advocates (71%) confirm that #MeToo and coverage of sexual violence in the news, social media, or television contribute to their STS. Fewer advocates (34%) experience burnout, which is attributed to workload. Advocates cope by reaching out to others (colleagues, friends, and family) and exercising.